On the Growing up of Autistic Individuals. On the Growing up of Autistic Individuals - S. Shore (Moscow State University of Psychology and Education, 2020)
The Introduction word by the thematic editor of the issue reveals the main current tasks related to the challenges of growing up individuals with autism spectrum disorders. A brief analysis of the content of thematic publications included in the current issue of the journal is carried out. A new rubric "Remote support for people with autism" introduced in connection with changes in living conditions caused by the COVID-19 epidemic is presented.